2008
DOI: 10.1152/ajpgi.90317.2008
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory mechanism governing the diurnal rhythm of intestinal H+/peptide cotransporter 1 (PEPT1)

Abstract: The intestinal H(+)/peptide cotransporter 1 (PEPT1) plays important roles as a nutrient and drug transporter. Previously, we reported that rat intestinal PEPT1 showed a diurnal rhythm and that this rhythm is closely related to the feeding schedule. Furthermore, we also demonstrated that transcription factors, Sp1, Cdx2, and peroxisome proliferator-activated receptor-alpha (PPAR-alpha) contribute to the basal, intestine-specific, and fasting-induced expression of PEPT1, respectively. In this study, to clarify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 39 publications
0
48
1
Order By: Relevance
“…Previous studies using PPAR␣-null mice demonstrated that Slc15a1 is typical of PPAR␣ target genes whose expression oscillates in a circadian time-dependent as well as feeding state-dependent manner (28). Although a molecular component of circadian clock has been shown to govern the daily expression of Slc15a1 in laboratory rats (12), the present study demonstrated that the suppressing action of bile acids on PPAR␣ activity is involved in the circadian regulation of the expression of Slc15a1 in mouse intestinal epithelial cells.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Previous studies using PPAR␣-null mice demonstrated that Slc15a1 is typical of PPAR␣ target genes whose expression oscillates in a circadian time-dependent as well as feeding state-dependent manner (28). Although a molecular component of circadian clock has been shown to govern the daily expression of Slc15a1 in laboratory rats (12), the present study demonstrated that the suppressing action of bile acids on PPAR␣ activity is involved in the circadian regulation of the expression of Slc15a1 in mouse intestinal epithelial cells.…”
Section: Discussioncontrasting
confidence: 46%
“…For example, it has been reported that intestinal expression of PepT1 is regulated by insulin, thyroid hormone, epidermal growth factor, and some pharmacological agents (8 -11). In laboratory rodents, the levels of Slc15a1 mRNA and PepT1 protein fluctuate in a time-dependent manner (12), suggesting that the expression of Slc15a1/PepT1 is under the control of a circadian clock.…”
mentioning
confidence: 99%
“…For example, apical Na + /glucose cotransporter 1 (SGLT1) and fructose transporter 5 (GLUT5) as well as the basolateral hexose transporter GLUT2 show rhythmic expression (31)(32)(33)(34)(35)(36). In addition, the expression of protoncoupled, oligopeptide transporter 1 (PEPT1), which is also a nutrient and drug transporter, shows diurnal expression ( 32,37 ). We reported that intestinal and hepatic gene expression of microsomal triglyceride transfer protein (MTP), a protein involved in intracellular neutral lipid transfer ( 38,39 ), shows rhythmic expression ( 40 ).…”
Section: Determination Of Mtp Activitymentioning
confidence: 99%
“…Recent studies indicate that circadian changes in the expression of epithelial transporters might be controlled by the core clock mechanism. This has been demonstrated for the Na ϩ /H ϩ exchanger NHE3, the peptide transporter PEPT1, and monosaccharide transporters SGLT1, GLUT2, and GLUT5 in the intestine (23,28,33) and for NHE3 and the ␣-subunit of the epithelial Na ϩ channel (ENaC) in the renal tubules (7,27). Approximately 3.7% of distal colonic genes are expressed rhythmically (11).…”
mentioning
confidence: 95%